"Singing the Strong Light Works of [American] Engineers": Popular Histories of the Internet as Mythopoetic Literature. - Katz-Kimchi, Merav (Information & Culture, 2015)
During the 1990s, when the Internet became a common communication medium in the United States, its history was recounted in numerousworks that were intended for popular American audiences. In the context of the new legitimizing discourse of the technopolitical order of post-Fordist society, which views network technology at the center of an emancipatory social transformation, this article critically analyzes the role of the authors, as well as the main characters, actions, plot, and narrative of these works. The authors wrote for specific intended audiences, casting the history of the Internet into the mythopoetic form of the technological romance that dramatizes the eroticized prodigious work of the so-called Internet pioneers.